The effect of plant growth promoting Rhizobacteria treatment on germination and seedlings growth of chilli - SYAMSUDDIN SYAMSUDDIN; SITI HAFSAH; VINA MAULIDIA; AINUN MARLIAH (Jurnal Natural, 2022)
The aim of the research was to study the effects of biological seed treatment utilization rhizobacteria on seed germination and seedling growth, furthermore to figure out the competence of rhizobacteria isolates to dissolve phosphate, produce acetic indol acid (IAA) and siderophore. 18 rhizobacteria isolates used in this research, each isolates was anlayze in vitro; IAA, phosphate and siderophore. Then carried out the in vitro test, the pepper seeds were inoculated with rhizobacteria isolates suspension then germinated. Seedlings were transpalated into a plastic pot filled with medium soil and compost (2:1). The germination was observed everyday until 14 days, the seedlings was observed at 4 and 6 weeks after transplating. Based on the study, all the rhizobacteria isolates produced IAA, 13 rhizobacteria isolates capable to dissolve phosphate and 12 rhizobacteria isolates produced siderophore. Seed treatment using RBNA 14, RBNA 13, RBKB 5, and RBSPA 14 adequate to increase the germination in seed viability and vigor also increase seedling growth